2016
DOI: 10.1039/c6fd00035e
|View full text |Cite
|
Sign up to set email alerts
|

Fast and selective separation of carbon dioxide from dilute streams by pressure swing adsorption using solid ionic liquids

Abstract: The need to create a new approach to carbon capture processes that are economically viable has led to the design and synthesis of sorbents that selectively capture carbon dioxide by physisorption. Solid Ionic Liquids (SoILs) were targeted because of their tunable properties and solid form under operational conditions. Molecular modelling was used to identify candidate SoILs and a number of materials based on the low cost, environmentally friendly acetate anion were selected. The materials showed excellent sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…first allowing gas adsorption for 15 min at 15 bar. Previous work (Dowson et al, 2016) has shown that after this 15-min period, the sorbent will be fully saturated at 100% and will adsorb no more as shown in Figure 9. In fact, adsorption rates for some of the ionic liquid sorbents were found to be mere seconds.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…first allowing gas adsorption for 15 min at 15 bar. Previous work (Dowson et al, 2016) has shown that after this 15-min period, the sorbent will be fully saturated at 100% and will adsorb no more as shown in Figure 9. In fact, adsorption rates for some of the ionic liquid sorbents were found to be mere seconds.…”
Section: Resultsmentioning
confidence: 96%
“…This composition sits well within the range expected as an output from coal fired power stations, for example, found in the UK (Naims, 2016;von der Assen et al, 2016). This PSA system makes use of a cheap and robust solid sorbent, which is based on previously reported poly-ionic liquid sorbents by this group (Supasitmongkol and Styring, 2010;Dowson et al, 2016), which selectively adsorbs CO2 on pressurization of the gas stream. As the pressure is released, the N2 and CO2 desorb from the sorbent surface at different rates, thus creating two separate streams; one rich in N2 followed by one rich in CO2.…”
Section: Methods Pressure Swing Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique physicochemical properties of these materials place them in the first row of choice as solvent for numerous applications like organic reactions, photochemical reactions, energy devices etc. Trifluoro acetate and trifluoromethane sulphonate anion based protic and aprotic ILs have been used for various applications by different research group such as catalyst and reaction medium for the Fischer indole synthesis; as chiral catalysts for the enantioselective Michael addition reaction; alternative electrolytes for rechargeable aluminium batteries; carbon dioxide, sulphur oxide and carbon capturing . The intermolecular interactions (like; hydrogen bonding, Coulomb charge and dispersion forces) and fundamental properties of ILs are key features to understand the mechanism behind the usability.…”
Section: Introductionmentioning
confidence: 99%
“…This is evident where an energetic driving force is required for either the sorption of the carbon dioxide, such as in high pressure adsorption and membrane separation, or for the desorption step, such as in amine-based chemisorption or vacuum swing adsorption. This results in a range of energy costs from approximately 1 to 4 GJ/t CO2 with the lower range consisting mainly of immature techniques and the upper range consisting of benchmark amine processes such as monoethanolamine (Dowson et al, 2016). Further issues associated with the capture processes involve the challenges of retrofitting existing plants and the footprint size of the capture process facility, which must be sited near to the point source, as well as the interactions between the sorbent materials and trace gases in the waste stream which are often corrosive or deleterious, especially to the benchmark amine sorbent materials (Uyanga and Idem, 2007;Soosaiprakasam and Veawab, 2008).…”
Section: The Cost Of Carbon Capturementioning
confidence: 99%